Nanolithography on the Electron Beam Resist using the Scanning Probe Microscope Cantilever - Lydia Anggraini; Naoki Matsuzuka; Yoshitada Isono (Journal of Mathematical and Fundamental Sciences, 2010)
This research demonstrates the feasibility of fabricating nanoscale resist patterns on a silicon (Si) substrate using a scanning probe microscope (SPM). In order to utilize scanning probe nanolithography (SPNL) with the other micro-machining techniques such as dry etching, plating and lift-off process, nanoscale resist patterns should be created on an Si substrate with high accuracy in SPNL. We have, so far, established the negative type of SPNL using the negative-tone electron beam (EB) resist named SAL601. The primary objective of this research is to find out appropriate process conditions for establishing the positive type of SPNL using the positive EB resist "³ZEP520A"³. This paper describes the variations of experimentally created nano-patterns depending on the process conditions, and determines the appropriate process conditions from the variations obtained. In addition, we analyzed the electric field in the EB resist by a finite element method (FEM), for estimating the line width of the nano-pattern created by SPNL.